Effects of physical exercise on survival after allogeneic stem cell transplantation - Wiskemann, Joachim; Kleindienst, Nikolaus; Kühl, Rea; Dreger, Peter; Bohus, Martin (International journal of cancer, 2015)
Observational studies have suggested that physical activity may be associated with improved survival after cancer treatment. However, data from controlled clinical trials are required. We analyzed survival data of 103 patients from a previously published randomized controlled trial in allogeneic stem cell transplant patients who were randomized to either an exercise intervention (EX) or to a social contact control group. EX patients trained prior to hospital admission, during inpatient treatment, and for 6-8 weeks after discharge. Survival analyses were used to compare both total mortality (TM) and non-relapse mortality (NRM) after discharge and transplantation during an observation period of 2 years after transplantation. Analyses were corroborated with Cox and Fine & Gray regression models adjusting for potential confounders. After discharge, EX patients had a significantly lower TM rate than controls (12.0 vs. 28.3%, p = 0.030) and a numerically lower NRM rate (4.0 vs. 13.5%, p = 0.086). When the inpatient period was included, absolute risk reductions were similar but not significantly different (TM: 34.0 vs. 50.9%, p = 0.112; NRM: 26.0 vs. 36.5%, p = 0.293). The number needed to treat (NNT) to prevent one death with EX was about 6. Furthermore, regression analyses revealed that baseline fitness was protective against mortality. The data suggest that exercise might improve survival in patients undergoing allo-HCT. However, the results should be interpreted with caution as the study was not designed to detect differences in survival rates, and as no stratification on relevant prognostic factors was carried out.